MICROECONOMIC ANALYSIS IN COMPETITION POLICY - Paul Prisecaru (Global Economic Observer)
This paper presents some of the most important microeconomic tools used in assessing antitrust and merger cases by the competition authorities. By explaining the way that microeconomic concepts like “market power”, “critical loss” or “price elasticity of demand” are used by the modern competition policy, the microeconomics scholar can get a practical perspective on the way that these concepts fit into the more general concept of “competition policy”. Extensive economic research has shown what are the market forces and economic factors that determine how cartels, which are at the core of antitrust policy, are established and sustained over time. One of the most important of these factors is the markets exposure to innovation, especially disruptive innovation. In these markets, the paradox, from a competition policy perspective, can be considered the fact that collusion is one of the least important concerns, due to the specific elements that determine the nature of competition.Instead, the main anticompetitive risk in the markets exposed to intensive innovation is unilateral conduct by which dominant incumbents can exclude competitors.